Effects of tocilizumab on neutrophil function and kinetics. (31st August 2017) - Lok, Laurence S. C.; Farahi, Neda; Juss, Jatinder K.; Loutsios, Chrystalla; Solanki, Chandra K.; Peters, Adrien M.; Donaldson, Francis; Porter‐Brown, Benjamin; Chilvers, Edwin R.
Abstract: Background: Decreases in circulating neutrophils (polymorphonuclear leucocytes, PMNs) have been reported in patients treated with the anti‐interleukin‐6 receptor (IL‐6R) antibody tocilizumab (TCZ); the mechanism for this is unclear. We hypothesize that TCZ reduces circulating neutrophils by affecting margination and/or bone marrow trafficking without affecting neutrophil function or apoptosis. Materials and methods: Eighteen healthy subjects were randomized to single intravenous dose of TCZ 8 mg/kg ( n  = 12) or placebo ( n  = 6) on day 0. On day 4, each subject had autologous indium‐111‐labelled neutrophils re‐injected, and their kinetics quantified with longitudinal profiling in a whole body gamma‐counter. TCZ‐treated subjects were divided into two groups according to the extent of reduction in neutrophil count. Results: Mean day 4 neutrophil counts, as % baseline, were 101·9%, 68·3% and 44·2% in the placebo, TCZ‐PMN‐'high' and TCZ‐PMN‐'low' groups, respectively ( P  <   0·001). Following TCZ, neutrophil function, activation and apoptosis ex vivo were all unaffected. In vivo, there were no differences in early blood recovery or margination to liver/spleen and bone marrow; however, later neutrophil re‐distribution to bone marrow was markedly reduced in the TCZ‐PMN‐low group (peak pelvic count as % day 4 count on: day 5, 188% placebo vs. 127% TCZ‐PMN‐low, P  <   0·001; day 10, 180% placebo vs. 132% TCZ‐PMN‐low, P  <   0·01), with a trend towards higher liver/spleen neutrophil retention. Conclusions: We have demonstrated for the first time in humans that IL‐6R blockade affects neutrophil trafficking to the bone marrow without influencing neutrophil functional capacity.